THORACIC SURGERY Early results of a trimodality treatment for superior sulcus tumors - Łapiński, Mariusz; Dziadziuszko, Rafał; Sawicka, Wioletta; Rzyman, Witold (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction : Superior sulcus tumors are a unique form of lung cancer. Preoperative concurrent radio- and chemotherapy improves the results of treating these lung tumors. Aim: The study aimed to assess the early results of a trimodality treatment for superior sulcus tumors. Material and methods : Fifty-six superior sulcus tumors patients were operated on between 2006 and 2013. Data from 25 patients undergoing preoperative chemoradiotherapy were analyzed. Fifteen men and 10 women were treated (mean age: 59 years). All patients experienced pain in the pectoral girdle of the chest. Results: Nineteen patients received preoperative chemoradiotherapy consisting of 2 chemotherapy cycles with cisplatin (a different number of cycles was administered in 6 cases) and irradiation at a mean dose of 51.2 Gy (30-60 Gy) in 25 fractions (25-30 fractions). All patients underwent upper lobectomy. Twenty-two patients underwent chest wall resection, whereas 3 patients underwent extrapleural excision of the infiltrate without rib resection. Stages IIB and IIIB were diagnosed in 15 and 10 patients, respectively. In 9 samples, no neoplastic features were found, 9 showed individual neoplastic lesions, and in 7 most tumor cells were necrotized. The R1 resection was noted in 2 patients. Mean hospitalization time was 13 days. No perioperative deaths were noted. Conclusions : The trimodality treatment for superior sulcus tumors is a safe method. Perioperative mortality and the number of complications observed among patients treated with this method are similar to those observed in one-phase surgery. In over half of the patients, chemoradiotherapy resulted in complete or nearly complete remission of the neoplasm.